العدل الاجتماعی: مجالاتہ و آثارہ فی المجتمع الاسلامی: Social Justice, its Scope and Impact on Islamic Society - Hafiz Muhammd Tariq,; Muhammad Rafiq Sadiq, (Seerat Studies, 2023)
Justice is to give due rights to others without any prejudice, liking and disliking. Social justice is the name of truthful social system in which everyone enjoys and consumates equal opportunities of development and progress without any discrimination of caste, color, creed, power and religion. National resources are equitably allocated. No sensible person can deny the importance of social justice at individual or public level. This article highlights the impacts and fields of social justice with its definition and foundation in the light of teachings and life of the Prophet Mu╒ammad (SAW).